Analisis Penyusunan Laporan Keuangan Usaha Mikro, Kecil, dan Menengah Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah: Studi Kasus Pada Toko Utama Shoes - Aprilia Hidayati; Amaliah, Tri Handayani; Amir Lukum (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in driving the Indonesian economy. However, many MSMEs experience difficulties in preparing financial reports. To overcome this problem, the Indonesian Accounting Association (IAI) issued Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The purpose of this research is to find out how financial reports are prepared based on SAK EMKM at the Main Shoes Store. This research uses descriptive qualitative methods using primary data obtained through observation, interviews and documentation. The research results show that Toko Utama Shoes has not implemented SAK EMKM in preparing its financial reports. Limited human resources and poor understanding of SAK EMKM are the main obstacles in preparing financial reports based on SAK EMKM. This results in a lack of adequate information regarding operations and business profits. Therefore, researchers are trying to help Toko Utama Shoes to design and present financial reports based on SAK EMKM in accordance with theories and information related to the accounting cycle.